Financial activities of higher education institutions in Uzbekistan: analysis of revenue sources and expense structure - Khayriddinov Shukhrat Batirovich; Otaboeva Dzhumagul Rakhmatullaevna (THE INNOVATION ECONOMY, 2026)
This article examines the distinctive aspects of financial resource utilization in the field of higher education. The study highlights the financial conditions of state universities, emphasizing that a significant portion of the expenditures necessary for the functioning of higher education institutions is covered by state budget funds. This situation necessitates the establishment of a specific approach to the efficient and transparent allocation of these funds. The financing of higher education in Uzbekistan is carried out in two main forms: through allocations from the state budget and revenues generated from the provision of educational services